NUGGET BERBASIS SUSU KERBAU DENGAN PENAMBAHAN IKAN BILIH (Mystacoleucus padangensis) SEBAGAI MAKANAN TAMBAHAN TUMBUH KEMBANG BALITA: Uji Organoleptik dan Analisis Zat Gizi Nugget Berbasis Susu Kerbau dengan Penambahan Ikan Bilih (Mystacoleucus Padangensis) sebagai Makanan Tambahan Tumbuh Kembang Balita - Yahdillah, Honey; Diana, Fivi Melva; Helmizar, Helmizar (Amerta Nutrition, 2024)
Background: Bilih fish (mystacoleucus padangensis bleeker) is a local food source in West Sumatra with the potential to be one of the processed food products that can contribute to reducing stunting. Bilih fish contains complete nutrients for the growth and development of toddlers. Objectives: This research aims to (1) develop the formulas of buffalo milk-based nuggets with the addition of bilih fish, (2) select the best nugget formula based on an organoleptic test, and (3) analyse the nutritional content through tests (proximate, zinc, and calcium) in the formulas of buffalo milk-based nuggets with the addition of bilih fish as supplementary food for the growth and development of children aged 1-3 years (toddlers). Methods: The research design employed was experimental studies. The experimental design for the nugget formula was a Completely Randomised Design (CRD). The nugget formula was created with four treatment levels: F0 = standard formula (buffalo milk nugget + 0 g bilih fish), F1 (buffalo milk nugget + 10 g bilih fish), F2 (buffalo milk nugget + 30 g bilih fish), and F3 (buffalo milk nugget + 50 g bilih fish). The organoleptic test was conducted with 30 semi-trained panelists and 2 replications. The data collected were analysed by applying the Kruskal-Wallis and Mann-Whitney tests. Results: The best formula was F1, indicated by a bright yellow colour, savoury taste, aromatic smell, and tender texture. There were no significant differences among F0, F1, F2, and F3. The nutritional analysis results for F1 include water (46.90%), ash (2.32%), protein (11.77%), fat (7.60%), calcium (5.52 mg), and zinc (16.63 mg) per 100 g of nuggets. Conclusions: The best formula is F1 (buffalo milk nugget + 10 g bilih fish).